Modified Gene Editing Systems: Diverse Bioengineering Tools and Crop Improvement - Zhu, Guoning; Zhu, Hongliang (Frontiers in Plant Science, 2022)
Gene editing systems are emerging bioengineering tools in recent years. Classical gene editing systems include zinc-finger nucleases (ZFNs), transcription Activator-like effector nucleases (TALENs) and clustered regularly Interspaced short Palindromic Repeats (CRISPR) with CRISPR-Associated Protein 9 (Cas9) [CRISPR-Cas9], these tools allow specific sequences to be targeted and edited. On the basis of the classical gene editing systems, a variety of modified gene editing systems have been established. Base Editors(BEs) can accurately carry out base substitution on target sequences, while Prime-Editor(PE) can modify long fragments. In addition, CRISPR systems targeting mitochondrial genomes and RNA have also been explored and established. Based on CRISPR/Cas9, multiple gene editing techniques were established and applied to genome engineering. Modified gene-editing systems also make transgene-free plants more readily available. In this review,We discuss the modifications of gene editing system in recent years, and summarize the capability, deficiency and application of modified gene editing systems. Finally, we discuss the future development direction and challenges of modified gene editing systems.